Determination of isotope ratio in the divertor of JET-ILW by high-resolution Hα spectroscopy: H–D experiment and implications for D–T experiment. (11th February 2019) - Neverov, V.S.; Kukushkin, A.B.; Kruezi, U.; Stamp, M.F.; Weisen, H.
Abstract: The data of the H α high-resolution spectroscopy, collected on the multiple lines of sight, which cover the entire divertor space in poloidal cross-section, during the recent hydrogen-deuterium experiments in JET-ILW (ITER-like wall), are processed. A strong spatial inhomogeneity of the hydrogen concentration, H/(H  +  D), in divertor is found in many pulses. Namely, the H/(H  +  D) ratio may be lower in the inner divertor than that in the outer divertor by the values of 0.15–0.35, depending on the conditions of gas puffing and plasma heating. This effect suggests the necessity of spatially-resolved measurements of isotope ratio in the divertor in the upcoming deuterium–tritium experiments. Also, separation of the overlapped T α and D α spectral lines is shown to be a challenging task especially when the local Doppler-broadened (Gaussian) line shapes are noticeably distorted by the net inward flux of fast non-Maxwellian neutral atoms. We use the respective, formerly developed model of an asymmetric spectral line shape, while analysing the data of the first deuterium–tritium experiment in JET-C (carbon wall), and test the model via comparing the isotope ratio results with another diagnostic's measurements. This model is shown to increase the accuracy of tritium concentration measurements in the divertor.